In Vitro and In Vivo Effects of Light Therapy on Cartilage Regeneration for Knee Osteoarthritis: A Systematic Review. (December 2021) - Oliveira, Sofia; Andrade, Renato; Hinckel, Betina B.; Silva, Filipe; Espregueira-Mendes, João; Carvalho, Óscar; Leal, Ana
Objective: To analyze the effects of light therapy (LT) on cartilage repair for knee osteoarthritis (OA) treatment. Design: The PubMed, Embase, Scopus, and Web of Science databases were searched up to August 31, 2020 to identify in vitro and in vivo studies that analyzed the effects of LT on knee cartilage for OA treatment. The study and sample characteristics, LT intervention parameters and posttreatment outcomes were analyzed. Risk of bias was assessed using the Risk of Bias Assessment for Non-randomized Studies (RoBANS) tool. Results: Three in vitro and 30 in vivo studies were included. Most studies were judged as high risk of performance and detection bias. Biochemical outcomes were analyzed for both i n vitro and in vivo studies, and histological and behavioral outcomes were analyzed for in vivo studies. LT reduced extracellular matrix (ECM) degradation, inflammation, and OA progression, promoting ECM synthesis. LT improved pain-like behavior in animal models, having no apparent effect on gait performance. There were conflicting findings of some of the biochemical, histological, and behavioral outcomes. Conclusion: The included studies presented different strategies and LT parameters. LT resulted in positive effects on cartilage repair and may be an adequate therapy for OA treatment.